The HMGU combined neutron and photon dosemeter. (June 2017) - Wielunski, Marek; Trinkl, Sebastian; de Souza-Santos, Denison; Wahl, Wolfgang; Rühm, Werner
Abstract: Recently, two independent electronic dosimeters for individual monitoring have been developed at the Helmholtz Center Munich, Germany, one for photons and one for neutrons. Calibration of these dosimeters was performed using mono-energetic neutrons (energy range: 144 keV–14.8 MeV) and photons (12 keV–1.3 MeV), and the resulting calibration curves were compared to Monte Carlo simulations using the GEANT4 tool kit. In the present paper, an integrated dosimeter prototype is described which combines both dosimeters and therefore allows measurement of total dose in mixed neutron/photon radiation fields. It is demonstrated that the neutron channel of the combined dosimeter is insensitive to photons, while the photon channel is insensitive to neutrons. The prototype was tested in the field of an Am-Be neutron source which also includes a photon component. When the Am-Be neutron source was shielded by 9 mm lead, the combined dosimeter indicated a dose rate of 122.6 ± 1.0 μSv/h from neutrons and 7.3 ± 0.1 μSv/h from photons. In contrast, when the Am-Be neutron source was not shielded by lead, the combined dosimeter indicated a dose rate of 125.8 ± 1.0 μSv/h from neutrons and 65.9 ± 0.1 μSv/h from photons indicating a significant contribution from photons to total dose. In a second experiment when the Am-Be neutron source was closer to the combined dosimeter and a 137 Cs source was added, a neutron dose rate of 421 ± 20 μSv/h and a photon dose rate of 849 ± 6 μSv/h was obtained. It is concluded that this instrument can be used in mixed photon-neutron fields with doses and dose rates typical for radiation protection purposes. Highlights: An electronic personal dosimeter for mixed neutron and photon fields was developed. Neutron response was simulated and measured between thermal energies and 200 MeV. Photon response was simulated and measured between 12 keV and 1.3 MeV. Dosimeter was successfully tested in mixed AmBe-neutron and 137Cs-photon field.